(3JPcQI aj Yde GdgjFIs - (3eMeO Hf eMeO Hf GdMSf, CHh LYaQ, fUjQ GdOjf GdWhSj , J (B672 (3g` s
(3ChdgG (B:s
(3GdMeO ddg eSNQ GdNjQ hedge GdUhGH GdHGH GdChd ajeG jLH HYO dcd Yde ehVY GdHMK s
(3BNQgG (B:s
(3hGdKGfi CHYOgeG hgh HYO GdKhGHJ Yf eQcR GdCQV hdfNJJe GdcJGH ggfG MGeOjf ddg JYGdi s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdJGSY YTQs
(3GdfSNI HgG MhGTs
(3HgG CTcGd gfOSjIs
(3HgG fXGe GdJYbjHIs
(3Jdjg ahGFO s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B30 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B207s
Keywords: (3Gdadcs